A U-shaped spray device on a front boom-type roadheader for dust suppression in a metro tunnel. (February 2023) - Liu, Ning; Wu, Xiong; Deng, E.; Liu, Xinyuan; Wang, Youwu
Highlights: A new U-shaped spray device on a front boom-type roadheader for dust suppression in a urban metro tunnel is proposed. The reasonable type of nozzle are studied by indoor test. The dust diffusion law along the tunnel and the reasonable parameters of the device are studied. The proposed device has shown good performance in field tests. Abstract: The application of the cantilever tunneling method in urban metro tunnel constructions has been gradually promoted. High concentration of dust will be produced near the working face when a boom-type roadheader is used to excavate a small and narrow metro tunnel in hard rock. If not controlled in time, high concentration of dust will escape in the working wells, the air in cities will be polluted and the health of residents will be affected. To maintain the sustainable development of cities, a U-shaped dust suppression device with optimized nozzle arrangement installed at the front end of the boom-type roadheader is proposed in this study. Firstly, the atomization characteristics of four different types of nozzles were analyzed by an indoor model test. The optimum nozzle is determined to be a fine solid conical nozzle with a diameter of 1.6 mm. Then, the dust diffusion law in the core dust producing area under the action of an air compressor is analyzed based on the discrete phase model of computational fluid dynamics; the influence of the parameters of the complete spray device on the performance parameters of the droplet field is discussed in detail based on the Taylor analogy breakup simulation method. The results show that when the spray pressure is 8 MPa and the number of nozzles is 11, the formed droplet field has the best encapsulation and the high concentration droplets account for 77.36%. Finally, the device is applied and verified on site. The test results show that the maximum total dust suppression efficiency in the tunnel reaches 81.48%, the maximum respirable dust suppression efficiency reaches 81.51%, and the dust suppression efficiency at other monitoring points is also above 70.41%. Graphical abstract: Firstly, the dust samples collected on site were taken as the dust source, and the optimal nozzle type was determined through the indoor model test. Then, the optimal spray parameters of the U -shaped device without nozzles were obtained by establishing the airflow-droplet CFD-DPM coupling model. Finally, the optimal parameters of spray and the optimal nozzle are assembled into boom-type roadheader in engineering. By measuring the dust concentration before and after dust suppression on site, the dust suppression effect of the proposed device was verified. Image, graphical abstract